El movimiento lexicográfico hispanoamericano del siglo XIX y la creación de las academias correspondientes - Javier Pérez, Francisco (Círculo de Lingüística Aplicada a la Comunicación, 2026)
The purpose of this paper is to relate the creation of the corresponding academies of the Royal Spanish Academy during the last quarter of the nineteenth century with the progress that had been taking place for several decades in lexical studies on the Spanish language. In other words, it is intended to invert the order of the terms by understanding that the creation of the corresponding academies was the result of interests in lexicographic study and not that the foundation of these corporations was what motivated the rise of the discipline to elaborate dictionaries on American Spanish.